Глубинное шлифование деталей из труднообрабатываемых материалов - Силин С. С. Сергей Семенович; Хрульков В. А. Владимир Андреевич; Лобанов А. В. Анатолий Васильевич; Рыкунов Н. С. Николай Стефанович (Новости технологии)
На обороте тит. л. авт.